MacPublications Review - Darcy Meeker (Journal of Applied Communications, 1988)
Reviews of MacUser: The Macintosh Resource published by Ziff Davis; MACazine, Solutions for All of Us, published in Austin, TX; MacWORLD, The Macintosh Magazine; MacWEEK, The Workstation Weekly, published in San Francisco; Macintosh Today: Weekly News & Perspectives for Integrated Computer Solutions, PCW Communications, Inc.